1996
DOI: 10.1099/00222615-45-6-472
|View full text |Cite
|
Sign up to set email alerts
|

PCR detection of Toxoplasma gondii DNA in CSF for the differential diagnosis of AIDS-related focal brain lesions

Abstract: To evaluate whether the detection of Toxoplasma gondii DNA in CSF could contribute to the differential diagnosis of AIDS-related focal brain lesions, CSF samples from 88 HIVinfected patients (56 with focal brain lesions and 32 without) were tested prospectively by a nested PCR for the B1 gene of T. gondii. The assay had a detection limit of 10 trophozoite equivalents. Six of 18 patients with toxoplasmic encephalitis, but none of the 70 patients with other disorders, were PCR-positive (33.3% sensitivity and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
1
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 20 publications
0
31
1
3
Order By: Relevance
“…Second, all blood samples from patients with cerebral toxoplasmosis were collected before or on day 3 of specific therapy. Previous studies reported that anti-Toxoplasma therapy decreases diagnosis sensitivity, especially if samples are collected after the first week of treatment (9). Finally, most of the studied patients with cerebral toxoplasmosis presented severe immunodeficiency (less than 200 CD4 ϩ T lymphocytes/l).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, all blood samples from patients with cerebral toxoplasmosis were collected before or on day 3 of specific therapy. Previous studies reported that anti-Toxoplasma therapy decreases diagnosis sensitivity, especially if samples are collected after the first week of treatment (9). Finally, most of the studied patients with cerebral toxoplasmosis presented severe immunodeficiency (less than 200 CD4 ϩ T lymphocytes/l).…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of molecular diagnosis in cerebral toxoplasmosis is normally done in CSF samples. In general, the sensitivity of the PCR test is extremely variable (11.5 to 100%), but the specificity is high (96 to 100%) (9,11,15,29,30,36,38). Nevertheless, CSF collection is invasive and is inappropriate in a subset of patients with expansive cerebral lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in technical procedure between different laboratories can affect PCR results (11). We believe that some conditions contributed to raise sensitivity with our PCR assay.…”
Section: Discussionmentioning
confidence: 99%
“…ausreichend therapierten Residualzuständen persistiert eine intrathekale Antikörpersynthese oft über Jahre. Zur Beurteilung der Krankheitsaktivität und Therapiebedürftigkeit sind daher auch nicht erregerspezifische Kriterien wie die Zellzahl und -differenzierung im Liquor sowie die Schrankenfunktion zu berücksichti-gen. Nach erfolgreicher antibiotischer Therapie sind Zellzahl und Schrankenfunktionsstörung innerhalb von Wochen bis Monaten, der VDRL und das Treponemen-IgM innerhalb eines Jahres rück-läufig [91,92]. Die zerebrale Toxoplasmose ist eine der häufigsten opportunistischen Infektionen bei Patienten mit AIDS und einer CD4 + -T-Zellzahl < 100/µl.…”
Section: Opportunistische Infektionenunclassified
“…Die Toxoplasma-PCR hat nur geringe bis moderate Sensitivität (12 -64 %), wobei die Spezifität bei annähernd 100 % liegt. Ein negativer Befund schließt eine zerebrale Toxoplasmose nicht aus, sodass im Verdachtsfall und passender MRT-Bildgebung eine Therapie eingeleitet werden sollte [91,92].…”
Section: Opportunistische Infektionenunclassified